b - Brown, Dan; Siriwardhana, Kumara (Mirigama Ashirwada, 2019)
He saved the Catholic Church from a fundamentalist radical in Angels & Demons and exposed the world's greatest cover-up in The Da Vinci Code. Now, symbologist and Harvard professor Robert Langdon returns to uncover another mystery. Called to Washington D.C., Langdon must investigate the centuries-old secrets of the Freemasons. However, with treachery around every corner, will Langdon's eidetic memory and insurmountable knowledge of history be able to guide him through another adventure?
Keywords: Fiction; Novel; Translation; Freemasons -- Fiction; Freemasons